Análisis del Impacto de la Estrategia Feedback en los trabajadores de Yajá para el 2023 (2023)
The final objective of this research is to carry out the performance evaluation analysis using the 360 feedback strategy for the company Yajá SAS and also be able to contribute to organizational improvement and development in addition to enhancing activities, the importance of this exercise is in doing more efficient and effective management of the company's human capital and show results of the study as part of organizational management, since currently this resource is used to improve the work environment, this research is mixed in that it has both qualitative variables as quantitative and is carried out through the interview technique.